A novel transalveolar approach for retrieval of displaced tooth roots from the maxillary sinus using a modified suction catheter: technical note. (3rd September 2019) - Cheng, H.; Sproat, C.; Patel, N.
Abstract: Aims: The aim is to introduce a novel transalveolar technique for retrieval of tooth roots from the maxillary antrum using a modified flexible suction catheter. Method: The displaced root is confirmed using plain radiographs and the patient is placed on a preoperative antral regime of broad‐spectrum antibiotics, analgesics and nasal decongestants for one week. On the day of the operation, the precise location of the root is identified using a small volume pre‐operative cone beam computed tomogram (CBCT). A buccal mucoperiosteal flap is raised to allow visualisation and exploration of the existing extraction socket. The dentoalveolar socket is expanded using a fissure bur in a surgical handpiece to allow access to the sinus. A modified flexible fine bore suction catheter is inserted into the sinus and directed to the location of the root to enable retrieval. The socket is then flushed with saline until the root is dislodged and captured at the tip of the catheter. The socket is closed in a tension free manner with a buccal advancement flap. The antral regime prescribed pre‐operatively is continued for one week post‐operatively. Results: This technique is currently practised at Guy's Hospital under local anaesthetic, intravenous sedation and general anaesthetic. This minimally invasive technique preserves alveolar bone and offers fewer complications than the Caldwell‐Luc. It allows immediate retrieval of displaced tooth roots from the maxillary sinus and is best applied when healing has not yet taken place. Conclusion: The combination of CBCT and this transalveolar approach using a modified flexible suction catheter should be considered in all cases where roots are to be retrieved from the maxillary sinus to reduce surgical morbidity.